Investing in open: Canadian challenges in bibliodiversity - Jaclyn McLean; Ian Gibson (Insights: The UKSG Journal)
This opinion piece addresses ideas and philosophies for libraries to think about when investing collections funds. It discusses the current landscape of open access funded significantly by authors (via article processing charges (APCs)) or via library agreements to offset APCs, the continued dominance of legacy for-profit publishers and suggests some ways forward to influence change in the publishing landscape. Written with a Canadian lens, these recommendations will be relevant in other geographies as well, as the publishing landscape is global.